Climate Change as a Threat Multiplier of Forced Migration: Political Economy and Human Security in Coastal Communities of Sukabumi, Indonesia - Effendi, Irmawan; Irmawati, Irmawati (TEMALI : Jurnal Pembangunan Sosial, 2026)
This study analyzes how climate change functions as a threat multiplier that drives forced migration in the coastal areas of Sukabumi Regency, West Java, through a political economy lens and the human security framework. The study advances the argument that migration from coastal regions does not arise solely from natural disasters as physical threats, but from the cumulative process of environmental and economic vulnerability that gradually delegitimizes the viability of life in places of origin. Using a qualitative case study approach, the research collected data through in-depth interviews with key stakeholders—namely the Environmental Agency of Sukabumi Regency, the Sukabumi Office for the Protection and Services of Indonesian Migrant Workers (P4MI), the Sukabumi branch of the Indonesian Migrant Workers Union (SBMI)—as well as prospective migrants from coastal communities, and complemented these data with policy document analysis and official online sources. The findings show that climate change has tangibly undermined the economic base of coastal communities through the intensification of tidal flooding, rainfall instability, coastal abrasion, and infrastructure damage, which directly weakens the fisheries sector, coastal agriculture, and local tourism. These ecological disruptions precipitate the collapse of household economic security, as reflected in income volatility, rising debt burdens, and the narrowing of livelihood options, thereby framing migration as a survival rationality rather than a free choice of social mobility. In this context, migration frequently occurs through non-procedural channels, significantly increasing vulnerability to labor exploitation, human trafficking (tindak pidana perdagangan orang), and violence in destination countries. By applying the human security framework, this article demonstrates the simultaneous interconnections among environmental security, economic security, and personal security in the lived experiences of forced migration among Sukabumi’s coastal populations. The theoretical contribution of this study lies in conceptualizing forced migration not as a binary category, but as a spectrum of experiences shaped by structural pressures—climate change, political–economic inequality, and weak social protection—thereby positioning migration as a symptom of systemic failure in ensuring human security in coastal regions that are increasingly vulnerable to climate change.